2006
DOI: 10.1086/500842
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Cell Response to Antiretroviral Therapy in Children with Vertically Acquired HIV Infection: Is It Associated with Age at Initiation?

Abstract: We confirm the effectiveness of HAART with respect to the recovery of CD4 cell count and suggest a benefit of initiating ART before the age of 5 months. Age at initiation of the most-potent ART was not associated with the likelihood of sustaining the recovery of CD4 cell count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 26 publications
5
20
1
Order By: Relevance
“…Despite their greater rate of recovery, children failed to catch up to infant CD4% and CD4-for-age following two years of ART. This is consistent with previous studies[17,18,25,46,47]. A recent study from Uganda and Zimbabwe found lower CD4-for-age at ART initiation was associated with both older age at ART initiation and more rapid initial slope in CD4-for-age reconstitution; long-term predicted CD4 count was higher among children who initiated ART at a younger age in that study[19].…”
Section: Discussionsupporting
confidence: 91%
“…Despite their greater rate of recovery, children failed to catch up to infant CD4% and CD4-for-age following two years of ART. This is consistent with previous studies[17,18,25,46,47]. A recent study from Uganda and Zimbabwe found lower CD4-for-age at ART initiation was associated with both older age at ART initiation and more rapid initial slope in CD4-for-age reconstitution; long-term predicted CD4 count was higher among children who initiated ART at a younger age in that study[19].…”
Section: Discussionsupporting
confidence: 91%
“…Results were unconclusive. Four studies [25][26][27][28] concluded the absence of influence of age at baseline and five studies [14,23,[29][30][31] [16]. In our study, mean CD4 + % was normal in both cohorts.…”
Section: Discussionsupporting
confidence: 54%
“…Influence of age at baseline, independently of immunological status, was studied in European [23,[25][26][27][28][29] and a few African cohorts (1-8.7 years follow-up) [14,30]. Results were unconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Research associated with a low baseline CD4 cell count in both resource-rich 29,30 and lowincome countries. 9,10,12,13 Earlier access to treatment could prevent many deaths.…”
Section: M-f Anaky Et Al Paediatric Antiretroviral Therapy In Côte Dmentioning
confidence: 99%